Prospecção e diversidade taxonômica e funcional de comunidades microbianas associadas a ambientes contaminados com creosoto visando a formulação de consórcio bacteriano degradador desse composto - Aline Daniela Lopes Júlio (2019)
Creosote oil is a thick oily liquid formed from coal tar and has been widely used as the main preservative of wood structures in the industry for many decades. Due to the indiscriminate use, it was responsible for contaminations of surface soils and groundwater. These contaminated areas are a priority for remediation, because this contaminant consists of toxic, genotoxic and carcinogenic compounds such as polycyclic aromatic hydrocarbons (PAHs), heterocyclic polycyclic aromatic hydrocarbons (hetero-PAHs), phenolic compounds and benzene, toluene, ethylbenzene and xylenes (BTEXs). Among the treatment options for contaminated areas, bioremediation is considered to be an ecologically more sustainable and cost-effective choice. The success of the use of bioremediation is dependent on factors that bioestimulate contaminant degradation by the local microbiota or bioaumentation with inoculants that have mechanisms of tolerance to contaminants and high catabolic potentials. Molecular techniques have been shown to be powerful tools to know the structure of bacterial communities in these contaminated environments, guiding the implementation of bioremediation projects. The objective of this work was to study the bacterial community profile of aquifer liquid fraction and sediment samples contaminated with different creosote concentrations, to quantify the population of bacteria and archaea present in them and to evaluate bacteria isolated from the sediments for degradation of creosote to formulate a consortium composed of the isolates with greater catabolic potential, besides delineating the factors and conditions necessary to optimize the contaminant degradation in microcosmos with samples of the area. For the study, 8 samples of the aquifer liquid fraction and 5 sediment samples were collected in an area where an old old sleeper’s treatment and maintenance station (STS) of the Vitória/Minas railway it worked, located in the municipality of João Neiva/ES. The bacterial community profile of the aquifer liquid fraction samples was analyzed by Polymerase Chain Reaction-Denaturing Gradient Gel Electrophoresis (PCR - DGGE) and by the construction of 16S rRNA amplicon libraries and sequencing on the IlluminaMiseq platform (metataxonomic analyzes). In both, the profiles of the community were different between the samples and influenced by the presence of the contaminants, being possible to observe a deeper differentiation between the profiles of the samples without contamination and two of the samples with higher concentrations of the contaminants. From the metataxonomic analyzes it was also observed the negative correlation between the alpha diversity of the samples and the concentration of the contaminants and the enrichment of some taxa in the samples with high levels of contamination were also observed, especially the families Porphyromonadaceae, Gemmataceae and Comamonadaceae, and the genera Treponema, Geobacter, Bdellovibrio, Hydrocarboniphaga, Anaerolinea, Paulidibacter, Comamonas and Desulfomonille. The quantification of bacteria and archaea in these samples by Quantitative Real-Time PCR (qPCR) showed that the bacteria are numerically dominant in relation to archaea, and that two samples with high levels of contamination have a density significantly lower than the others. The profiles of the sediment samples were also different according to the PCR-DGGE technique and it was possible to observe the influence of the metadata in the grouping of them, with the separation of the structure of the 2 samples with the highest levels of contamination in relation to the others. Through the metataxonomic analyzes, it was also possible to observe the negative influence of the contaminants in relation to the richness and diversity of bacteria, as well as alteration of the profile of the bacterial community due to the enrichment of specific taxa in the sample with high contamination. Among these enriched taxa stands out representatives of the Gammaproteobacteria class, of the Acidobacteria phylum, mainly the families Koribacteraceae, Thermodesulfovibrionaceae, and the genus Candidatus Koribacter. The use of the PICRUSt tool allowed to predict the vii presence of enzymes and pathways related directly or indirectly to the degradation of hydrocarbons, as well as enzymes related to pathways that favor the survival of these microorganisms under field conditions. The quantification by qPCR showed that there was no statistical variation in bacterial cell density between the sediment samples and the presence of archaea was not detected. A total of 51 bacteria, most isolated from the sediment samples, were identified and evaluated for creosote degradation in MMM supplemented with this compound at 0.25% (v/v). In general, all isolates were able to degrade to some extent at least 1 creosote constituent and 27 isolates were able to degrade to some extent the 12 compounds present at the highest concentration in the creosote under study. The best degradation results were obtained for the isolates Comamonas terrigena (3FM6; 3FM8, 3FM9), Springobacterium sp. (1FM2; 5FM2), Bacillus sp. (2FM2, LAPM39), Pseudomonas sp. 3C10M3, Acinetobacter junii LAPM30, Pseudomonas plecoglossicida 3FM5, Bacillus subtilis LAPER93, Stenotrophomonas maltophila LAPER 27 and Enterobacter sp. 4FM2. These best isolates were evaluated for contaminant removal in sediment samples from the study area and contaminated with 1% creosote (v/v). Through this step it was determined that the consortium would be composed of S. maltophilla LAPER27, C. terrigena 3FM8, Springobacterium sp. 5FM2, Pseudomonas sp. 3C10M3, Bacillus sp. (2FM2, LAPM39), B. subtilis LAPER93 and Enterobacter sp. 4FM2. After this selection, 300 g of the creosote contaminated sediments samples 0.25% (v/v) were biostimulated under different conditions of aeration, nutrients and presence of the autochthonous microbiota, bioaumentation or not with the consortium and natural attenuation in microcosm assays for a period of 60 days. Through the statistical analyzes it was possible to confirm that the addition of the consortium and the presence of autochthonous microorganisms in the sample (non-sterilization) positively and significantly affected creosote degradation. However, the only significant interaction was between the factors sterilization + consortium + aeration, so although the aeration alone did not significantly influence the bioremediation, it was significant in the presence of these other two factors. The best treatments, predominantly those in which they had these conditions, promoted the highest average values of contaminant degradation, above 90%. The results obtained demonstrate that the study area is a candidate for remediation based on microorganisms by biostimulation, since it presents bacteria with high catabolic potential both in the liquid fraction of aquifer and in the sediment of the lagoon. However, the significance and increase in the mean creosote degradation in all the treatments in which there was a bioaumentation with the consortium developed, including those where the autochthonous microorganisms was present, suggests that the inoculant is able to optimize even more the bioremediation process. Thus, we suggest the use of these conditions for in situ bioremediation of the creosote-contaminated STS area.